Creativity and art therapies to promote healthy aging: A scoping review - Galassi, Flavia; Merizzi, Alessandra; D’Amen, Barbara; Santini, Sara (Frontiers in Psychology, 2022)
The purpose of this scoping review is to investigate the value of creative arts therapies in healthy older adults. This article aims to shed light on current knowledge concerning the effectiveness of art therapies (ATs) for the prevention of common age-related conditions using the definition of art therapy provided by the American Art Therapy Association (AATA), as well as Cohen’s conceptual framework for the psychological conceptualization of the relationship between the arts and health in later life. The objective is to carefully capture subthreshold situations of distress, which are often not taken into account and primarily involve psychological aspects that are crucial in the multidimensional perspective of healthy aging. Twelve articles were selected and examined following an initial electronic search on 3 databases. A thematic analysis of the results identified four major themes: improving cognitive performance and proprioception; enhancing self-identity and meaningful life; reducing feelings of loneliness and depressive symptoms; and the importance of socialization. All these aspects constitute the basis for preventing psychological distress and enhancing mental well-being for healthy aging.